The concept of livelihood according to Wahbah az-Zuhaili in Tafsir al-Munir and its relevance in the context of the Sandwich Generation - Marzuqi, Ahmad; Maulana, Ahmad Reynaldo; Badruzzaman, Abad; Akbar, A. Fadly Rahman (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2025)
Many people in contemporary society are “trapped” between two obligations that, in turn, trigger economic and psychological stress: supporting their nuclear family on the one hand, and supporting their unproductive parents on the other. This study examines the concept of sustenance according to Wahbah Az-Zuhali in Tafsir al-Munir, and its correlation with the social phenomenon of the sandwich generation. A thematic approach is used to explore the meaning of the verses about sustenance contained in Surah al-Baqarah: 215 and Surah An-Nisaa’: 34. Wahbah Az-Zuhali emphasizes that sustenance is a sharia obligation oriented towards justice and proportionality. This qualitative descriptive study focuses on Wahbah Az-Zuhali’s thoughts on who should provide sustenance and its correlation within the context of the Sandwich Generation. An inductive analysis of the Tafsir al-Munir literature illustrates that the concept of sustenance is highly relevant to the conditions of the Sandwich Generation, particularly in emphasizing the principles of social capability and responsibility. The command to sustenance needs to be understood flexibly and contextually to remain aligned with Qur’anic values ​​and address the challenges of the times.